1967
DOI: 10.3758/bf03331092
|View full text |Cite
|
Sign up to set email alerts
|

Imprinting or exposure learning in rats given early auditory stimulation

Abstract: Albino rats were raised from birth in an environment of music in an attempt to assess the effects of early exposure to specific musical forms on subsequent preference behavior. Ss were housed in groups in sound chambers. One group was exposed to selections of the music of Mozart for 12 hr. a day for 52 days; a second group to the music of Schoenberg. In the test situation when the Ss were given an opportunity to select Mozart or Schoenberg music, the Mozart Ss displayed a significant preference for Mozart musi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…This raises the possibility that the monkey's brain is innately wired to respond to tonal melodies. Rats (Cross, Halcomb, & Matter, 1967) and birds (Watanabe & Nemoto, 1998) have also been reported to show a preference for classical over atonal music (see "Affective Responses to Music?" section).…”
Section: Input From Comparative Psychologymentioning
confidence: 99%
“…This raises the possibility that the monkey's brain is innately wired to respond to tonal melodies. Rats (Cross, Halcomb, & Matter, 1967) and birds (Watanabe & Nemoto, 1998) have also been reported to show a preference for classical over atonal music (see "Affective Responses to Music?" section).…”
Section: Input From Comparative Psychologymentioning
confidence: 99%
“…Zajonc (1968) demonstrated that the mere exposure to a stimulus, e.g., a nonsense word, people, abstract and representational visual images, and types of music, increases people's liking of these stimuli. This exposure effect has also been demonstrated in rats (Cross, Halcomb, & Matter, 1967), suggesting that this is a deep-rooted principle in behavioural adaptation. Following a behaviouristic perspective, one would interpret this exposure effect as a strengthening of the stimulus± response relation between product and preference (e.g., Foxall, 1990).…”
Section: Consumer Behaviour and Changing Preferencesmentioning
confidence: 81%
“…En ce qui concerne le premier résultat obtenu, il concorde avec ceux d'études antérieures (Zajonc, 1997(Zajonc, , 2000Cross, Halcomb & Matter, 1967;Langer, Bashner & Chanowlzt, 1985;Rohmer & Louvet, 2000;Dovidio, Gaertner & Loux, 2000;Bless, 2009), qui supposent que les individus ayant un contact avec des personnes handicapées ont une attitude plus positive à leurs égards que leurs pairs qui n'entretiennent pas de relation avec ces dernières. Autrement dit, plus on a de contacts avec des personnes déficientes, plus nos attitudes envers elles deviennent positives.…”
Section: -Discussionunclassified